Raman threshold and optical gain bandwidth in silica fibers - Felinskyi, G.S.; Korotkov, P.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Nonlinearity of the stimulated Raman scattering (SRS) process in single-mode
fibers is the creation basis of the new class of modern photonic devices such as fiber
Raman lasers and fiber Raman amplifiers. The quantitative analysis of the gain start
conditions and the Raman laser threshold in the single mode fibers from the viewpoint of
the strong gain description of active laser materials have been made in this work. It has
been shown that the absolute transparency regime for optical transmission in fibers and
Raman laser threshold for a monochrome signal wave can be directly obtained from the
standard coupled equations using only fundamental fiber parameters. Limiting condition
when material of fiber core starts transformation from the natural state with attenuation
of the Stokes wave to the state in which the Stokes wave is amplified due to the pumping
power may be expressed in a simple analytical form. The numerical data of laser
threshold as a function of the wavelength and the examples of gain bandwidth
determination for several widespread Raman fibers have been presented.